Taxas Relacionadas, Derivadas como Transformações Lineares e Aplicações - VALADARES, Morgana Alcina Sales (Universidade Federal do Tocantins, 2023)
This work presents the derivatives of functions of several variables and highlights their appli- cations. Its main objective is to present two applications, namely, related rates and function